2003
DOI: 10.2337/diabetes.52.5.1280
|View full text |Cite
|
Sign up to set email alerts
|

A Common Polymorphism in the Promoter of UCP2 Contributes to the Variation in Insulin Secretion in Glucose-Tolerant Subjects

Abstract: It was reported that the common ؊866G/A polymorphism in the promoter of the human uncoupling protein-2 (UCP2) gene, which enhances its trascriptional activity, is associated with increased mRNA levels in human adipocytes and reduced risk of obesity. Studies in knockout mice and ␤-cells indicate that UCP2 may play a role in ␤-cell function. In this study, we addressed the question of whether the common ؊866G/A polymorphism in UCP2 gene contributes to the variation of insulin secretion in humans by genotyping 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
94
3
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 30 publications
12
94
3
3
Order By: Relevance
“…On the contrary, the AA genotype conferred an increased risk of type 2 diabetes (OR=1.84) in Italian women [22]. In line with that study, Sesti et al found that the A allele was associated with decreased glucose-stimulated insulin secretion in subjects with NGT as well as in human islets [43]. Here, we could not find any association between the −866G→A polymorphism and GDM in Scandinavian women despite the fact that our study had 99% power to detect the OR reported for the AA genotype in Italian women with type 2 diabetes [22], or for the G allele reported by Wang et al [20], as well as for the AA genotype reported in Caucasians [21].…”
Section: Irs1 G972rsupporting
confidence: 68%
“…On the contrary, the AA genotype conferred an increased risk of type 2 diabetes (OR=1.84) in Italian women [22]. In line with that study, Sesti et al found that the A allele was associated with decreased glucose-stimulated insulin secretion in subjects with NGT as well as in human islets [43]. Here, we could not find any association between the −866G→A polymorphism and GDM in Scandinavian women despite the fact that our study had 99% power to detect the OR reported for the AA genotype in Italian women with type 2 diabetes [22], or for the G allele reported by Wang et al [20], as well as for the AA genotype reported in Caucasians [21].…”
Section: Irs1 G972rsupporting
confidence: 68%
“…For example the −866A allele is associated with decreased insulin secretion in Caucasians from Italy [4], while the same allele was associated with increased secretion in Northern European Caucasians, as ascertained in Utah [5]. Another study reported a reduced risk of type 2 diabetes in obese middle-aged humans with a −866G allele [6].…”
Section: Discussionmentioning
confidence: 96%
“…In particular, VV genotype, in comparison to those who have the AA or A/V genotype, have a lower degree of uncoupling, lower energy expenditure (Astrup et al 1999), higher exercise energy efficiency (Buemann et al 2001), and lower fat oxidation. However, it has been reported that persons with the I/D genotype have an increased basal metabolic rate, increased 24-h energy expenditure and decreased BMI (Esterbauer et al 2001), as well as a low deposition index (Walder et al 1998).Recently, the −866 G-allele has been described to influence UCP2 transcription, to be associated with reduced adipose tissue mRNA expression, reduced transcriptional activity in vitro and in vivo, high BMI, fat mass changes (Yoon et al 2007), increased risk of obesity (Esterbauer et al 2001;Argyropoulos and Harper 2002;Vogler et al 2005), increased insulin response to glucose and reduced risk of T2D (Krempler et al 2002;Esterbauer et al 2001;Sesti et al 2003).…”
Section: Introductionmentioning
confidence: 99%